Condição nutricional de peixes em um reservatório neotropical, Brasil. - Moura, Sandra Maria Lopes de (2010)
This study was to evaluate the nutritional condition of five fish species in Manso Reservoir (14º32' - 15º40'S and 54º40' - 55º55'W), MT, during four years (march/2000 to february/2003) after impoundment. The premise consisted in high food availability just after impoundment (year I) provides better nutritional conditions to fish than subsequent years. Fish were sampled by nets of different mesh sizes. After the harvest, they were measured (standard length, cm) and weigh ( gutted weigh, g). The condition was calculated only for adults, through the residues generated by the gutted weight (WG) and standard length (SL), for each sex. Psectrogaster curviventris and Schizodon borellii nutritional condition were higher in the first year; Auchenipterus osteomystax and Pimelodus maculatus, in the second and Acestrorhynchus pantaneiro in the last two. In the second year the worst condition was recorded for A. pantaneiro, P. curviventris and S. borellii. The females of P. curviventris and S. borellii showed higher rates than males in four years. The other species didn't show any pattern in relation to this factor. Males A. pantaneiro showed higher rates in the first two years, while females in the last two; females A. osteomystax in the II year and males in the III year; females P. maculatus in the first two and males in the last two. Thus, it is possible to infer that, except for A. pantaneiro, the nutritional condition of the other species were better in the first two years, and that variable sex showed a pattern of only two analyzed species. This suggests that each one shows its own specific particularities and respond differently to disturbance imposed by impoundments.